Cognitive test battery for evaluating elderly Chinese Americans. (2nd October 2018) - Li, Clara; Neugroschl, Judith; Zhu, Carolyn W.; Umpierre, Mari; Martin, Jane; Zeng, Xiaoyi; Huang, Qiying; Grossman, Hillel; Cai, Dongming; Sano, Mary
ABSTRACT: Objectives: This study aimed to determine the diagnostic utility of a Chinese test battery for evaluating cognitive loss in elderly Chinese Americans. Methods: Data from a pilot study at the Mount Sinai Alzheimer's Disease Research Center was examined. All participants were > 65 years old, primarily Chinese speaking, with adequate sensorimotor capacity to complete cognitive tests. A research diagnosis of normal mild cognitive impairment (MCI) or Alzheimer's disease (AD) was assigned to each participant in consensus conference. Composite scores were created to summarize test performance on overall cognition, memory, attention executive function, and language. Multivariable logistic regression models were used to assess the sensitivity of each cognitive domain for discriminating three diagnostic categories. Adjustment was made for demographic variables (i. e., age, gender, education, primary language, and years living in the USA). Results: The sample included 67 normal, 37 MCI, and 12 AD participants. Performance in overall cognition, memory, and attention executive function was significantly worse in AD than in MCI, and performance in MCI was worse than in normal controls. Language performance followed a similar pattern, but differences did not achieve statistical significance among the three diagnostic groups. Conclusions: This study highlights the need for cognitive assessment in elderly Chinese immigrants.